Potential Residual Contaminants in Edible Bird's Nest - Yeo, Bee-Hui; Tang, Teck-Kim; Wong, Shew-Fung; Tan, Chin-Ping; Wang, Yong; Cheong, Ling-Zhi; Lai, Oi-Ming (Frontiers in Pharmacology, 2021)
Edible bird’s nest (EBN) is recognized as a nourishing food among Chinese people. The efficacy of EBN was stated in the records of traditional Chinese medicine and its activities have been reported in many researches. Malaysia is the second largest exporter of EBNs in the world, after Indonesia. For many years, EBN trade to China was not regulated until August 2011, when a safety alert was triggered for the consumption of EBNs. China banned the import of EBNs from Malaysia and Indonesia due to high level of nitrite. Since then, the Malaysian government has formulated Malaysian Standards for swiftlet farming (MS 2273:2012), edible bird’s nest processing plant design and management (MS 2333:2010), and edible bird’s nest product quality (MS 2334:2011) to enable the industry to meet the specified standards for the export to China. On the other hand, Indonesia's EBN industry formulated a standard operating procedure (SOP) for exportation to China. Both countries can export EBNs to China by complying with the standards and SOPs. EBN contaminants may include but not limited to nitrite, heavy metals, excessive minerals, fungi, bacteria, and mites. The possible source of contaminants may come from the swiftlet farms and the swiftlets or introduced during processing, storage, and transportation of EBNs, or adulterants. Swiftlet house design and management, and EBN processing affect the bird’s nest color. Degradation of its optical quality has an impact on the selling price, and color changes are tied together with nitrite level. In this review, the current and future prospects of EBNs in Malaysia and Indonesia in terms of their quality, and the research on the contaminants and their effects on EBN color changes are discussed.